Feeling of Safety among Residents in Metropolitan Lagos, Nigeria - ADEJOH, PIUS (Advances in Social Sciences Research Journal, 2019)
Abstract This study examines the social factors that underpin the feeling of safety among residents in metropolitan Lagos. The paper is anchored on the instrumental and expressive theories of fear of crime and feeling of safety. It utilized quantitative data that were generated from 1,107 community members aged 18 who were drawn from four Local Government Areas of Lagos state. The study found a strong positive association between sex, employment, ethnicity, income; perceived neighbourhood crime level, experience of victimization, neighbourhood disorderliness and feeling of safety.It was recommended that relevant agencies of government-the police especially, must strive harder to improve citizens’ feeling of safety, because of its profound implications for the flourishing of democracy, economic development, social capital, associational life and the quality of life.